2023
DOI: 10.20935/acadbiol6073
|View full text |Cite
|
Sign up to set email alerts
|

Damage symptoms, development, and reproductive performance of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) on fodder maize and cob

Abstract: The biggest threat to maize production in recent years is the invasion of a new exotic pest fall armyworm (FAW), Spodoptera frugiperda (Lepidoptera: Noctuidae). Therefore, this study aimed to evaluate the damage characteristics, development, and reproductive preferences of this pest when its larvae fed on fodder maize and cobs. In this context, weights (g) of larvae, pupae and adults, pupal period (days), sex ratio (%), longevity (days), oviposition preferences, fecundity (%), egg incubation period (days), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…remus and T. foersteri on S. frugiperda eggs was reduced in egg masses with two layers compared to those with one layer. Similar findings have been observed in other parasitoid species Mohamed et al, 2023). For example, the number of eggs parasitized by T. atopovirilia Oatman & Platner and T. pretiosum Riley was higher in single-layer egg masses than in those with two layers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…remus and T. foersteri on S. frugiperda eggs was reduced in egg masses with two layers compared to those with one layer. Similar findings have been observed in other parasitoid species Mohamed et al, 2023). For example, the number of eggs parasitized by T. atopovirilia Oatman & Platner and T. pretiosum Riley was higher in single-layer egg masses than in those with two layers.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the number of eggs parasitized by T. atopovirilia Oatman & Platner and T. pretiosum Riley was higher in single-layer egg masses than in those with two layers. Likewise, a decrease in the parasitism of Trichogrammatoidea bactrae Nagaraja was observed when the parasitoid had access to egg masses containing more than 250 eggs arranged in two or three layers (Mohamed et al, 2023). Generally, variations in parasitism in egg masses with multiple layers are attributed to the inability of certain parasitoids to parasitize the eggs in the lower layers, except for those located at the edge of the egg masses, which can be easily reached from the side (Carneiro & Fernandes, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was observed that the fecundity of the FAW was relatively high and comparable to that of previous studies conducted under similar conditions [27,[34][35][36]. Moreover, just like the established life cycle of the FAW, each larva in this experiment went through six instar stages.…”
Section: Discussionsupporting
confidence: 87%